Penerapan Model Pembelajaran Kooperatif Tipe Numberead Head Together Untuk Meningkatakan Hasil Belajar Siswa Pada Tema 8 Lingkungan Sahabat Kita Kelas V SD - Rasmi Djabba; Ritha Tuken; Mutmainnah Mutmainnah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The problem discussed in this study is to apply a numbered head together (NHT) type of cooperative learning model to improve the process and learning outcomes of science for fifth-grade students of SD Negeri 3 Passeno. The aim to be achieved is to determine the application of the numbered head together (NHT) type of cooperative learning model to improve the process and learning outcomes of science learning for fifth grade students of SD Negeri 3 Passeno. This study uses a qualitative approach with this type of research is classroom action research (CAR). The results of this study indicate that the process and student learning outcomes in science learning after the application of the numbered head together (NHT) type of cooperative learning model. This shows that the numbered head together (NHT) type of cooperative learning model improves the process and learning outcomes of students in class V SD Negeri 3 Passeno.